MANAJEMEN PEMBERDAYAAN GURU DALAM LEMBAGA PENDIDIKAN ISLAM - Aris Sofandi (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2019)
Islamic Educational Institutions quality are related to its teachers’ quality. Qualified teacher will be able to help the institution to reach its vision. There are not a lot of good teachers. Therefore, the Islamic institution should apply teacher empowerment management system in order to increase the number of empowered and qualified teacher. Planning, organizing, actuating, and controlling are the main functions in management. Strategies to empower teacher are analysis and design of work, human resource planning, recruitment, selection, professional development, compensation, and work culture.